Tectonics, Climate, and Landscape Evolution 2006
DOI: 10.1130/2006.2398(20)
|View full text |Cite
|
Sign up to set email alerts
|

Downstream development of a detrital cooling-age signal: Insights from <sup>40</sup>Ar/<sup>39</sup>Ar muscovite thermochronology in the Nepalese Himalaya

Abstract: The character and distribution of cooling ages in modern river sediment provide useful constraints on rates and patterns of uplift and erosion within actively deforming mountain ranges. Such sediment effectively samples all locations within the catchment area, irrespective of remoteness. We evaluate how successfully detrital cooling ages may be used to constrain hinterland erosion rates by examining the modern catchment of the Marsyandi River in central Nepal. Over the 100-200-km-length scale of the catchment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
85
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(87 citation statements)
references
References 59 publications
2
85
0
Order By: Relevance
“…Monazites from graphic schists in the Lesser Himalayas revealed a range of early to mid-Miocene age (15.8-11 Ma) [Catlos et al, 2001]. Cooling ages of detrital muscovites from two catchment areas in Nepal also provided age ranges between 11 to about 20 Ma, having the upper ages that drained from the top of the Higher Himalayas and the Manaslu Granite [Brewer et al, 2006]. Fission track and U/Pb studies provide evidence for widespread cooling in the Nepalese Himalaya at about 16.0 ± 1.4 Ma, that is likely related to a combination of tectonic and erosional activity, including movement on MCT and Southern Tibetan Detachment System .…”
Section: Results and Interpretationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Monazites from graphic schists in the Lesser Himalayas revealed a range of early to mid-Miocene age (15.8-11 Ma) [Catlos et al, 2001]. Cooling ages of detrital muscovites from two catchment areas in Nepal also provided age ranges between 11 to about 20 Ma, having the upper ages that drained from the top of the Higher Himalayas and the Manaslu Granite [Brewer et al, 2006]. Fission track and U/Pb studies provide evidence for widespread cooling in the Nepalese Himalaya at about 16.0 ± 1.4 Ma, that is likely related to a combination of tectonic and erosional activity, including movement on MCT and Southern Tibetan Detachment System .…”
Section: Results and Interpretationsmentioning
confidence: 99%
“…Both studies have suggested a Himalayan contribution of the detritus. Based on thermochronometry, Brewer et al [2006] show that modern sediment from the Higher Himalayan sequences yield muscovite ages of circa 4-10 Ma, indicating recent erosion rates of ∼2 mm/yr or higher. The present study indicates there was a major influx of sediment to the Bengal basin at circa 16-18 Ma, consistent with the rapid unroofing event deduced by Harris et al [2004] for the Sikkim Himalaya.…”
Section: Results and Interpretationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermochronology of detrital minerals is a valuable tool for the reconstruction of regional patterns of erosion (Carrapa et al, 2009;Garver et al, 1999;Lonergan and Johnson, 1998;Najman et al, 2008;Rahl et al, 2007;Renne et al, 1990;Stuart, 2002;Vermeesch et al, 2006). A relatively recent development has been the use of thermochronologic data for modern stream sediment samples to approximate bedrock cooling age distributions (Huntington andHodges, 2006), paleorelief (McPhillips andBrandon, 2010;Stock and Montgomery, 1996), and erosion rates (Brewer et al, 2003(Brewer et al, , 2006Bullen et al, 2001). Ruhl and Hodges (2005) demonstrated how comparisons of detrital mineral cooling age distributions from modern sediments could be compared with catchment hyposometry to evaluate the evidence for topographic steady state and, if steady-state conditions were indicated, to extract robust estimates of Steady-state temperature structure beneath a periodic topography as calculated using the algorithms of Mancktelow and Grasemann (1997).…”
Section: Detrital Mineral Thermochronologymentioning
confidence: 98%
“…Provenance studies based on detrital geochronological techniques are a powerful tool to investigate the present-day pattern of erosion in mountain ranges (e.g. Hurford & Carter 1991;Garver et al 1999;Bernet & Spiegel 2004;Brewer et al 2006). In the Alpine belt, systematic analysis of bulk composition, ranking of metamorphic lithic grains, heavy-mineral assemblages and detrital zircon fission-track (FT) ages suggest that modern river sediments are characterized by specific end-member detrital modes, and they derive from small portions of the drainage where erosion rates are one order of magnitude higher than in surrounding areas (Bernet et al 2001(Bernet et al , 2004aVezzoli 2004;Vezzoli et al 2004;Malusà & Vezzoli 2006).…”
mentioning
confidence: 99%